INFLASI DAN SUKU BUNGA TERHADAP STOCK RETURN : PERAN MEDIASI DARI ROA - Rahmatika, Siti; Feranita, Nungky Viana (Universitas Muhammadiyah Parepare, 2021)
Since the establishment of the Indonesia Stock Exchange (IDX) capital market in 2007, based on the IDX president director's report, the results of the merger between the Jakarta Stock Exchange (JSX) and the Surabaya Stock Exchange (BES) have increased market capitalization by 103.84% with daily stock transactions. increased by 131.8%. These results reflect strong global investment sentiment and attract investors for large expected returns. Where the higher the expected return value, the greater the level of risk that might occur and become the basis for consideration for investors. The purpose of this research is to analyze the effect of inflation and interest rates as independent variables on stock return as the dependent variable and how big the role of ROA is as a mediator between the independent variables and the dependent variable. The population in this study was 188 financial statements of mining companies listed on the Indonesia Stock Exchange in 2018. The sampling in this study used a purposive sampling technique. The analytical method was path analysis using IBM SPSS 16 software. There are 3 accepted hypotheses and 4 of them are rejected. Testing the direct influence hypothesis shows that two paths have a significant effect, namely interest rates on ROA and interest rates on stock returns. Testing the indirect effect hypothesis shows that there is one path that has a significant effect, namely interest rates on stock returns through ROA.